1997
DOI: 10.1016/s0009-9236(97)90065-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of subcutaneous recombinant human interleukin-10 in healthy volunteers*

Abstract: Interleukin-10 inhibits T-lymphocyte activation and proliferation and lipopolysaccharide-induced monocyte production of proinflammatory cytokines. Fifty-four healthy volunteers received single doses of recombinant human interleukin-10 (1.0, 2.5, 5.0, 10, 25, or 50 micrograms/kg) or placebo by subcutaneous injection (randomized double-blind assignment). Clinical adverse events were infrequent at doses below 50 micrograms/kg (five of six subjects had mild flu-like syndrome). Mean serum interleukin-10 concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 29 publications
8
79
0
1
Order By: Relevance
“…Our data confirm that IL-10R1 is functional during embryonic development in response to its cognate ligand, causing an increase in leukocytes. Similarly, drIL-10 overexpression also causes an increase in leukocytes, which is consistent with its role in other systems (7,21). Importantly, we have shown that khvIL-10 could also increase leukocyte numbers in this heterologous setting, acting via the IL-10 receptor subunit, IL-10R1.…”
Section: Resultssupporting
confidence: 89%
“…Our data confirm that IL-10R1 is functional during embryonic development in response to its cognate ligand, causing an increase in leukocytes. Similarly, drIL-10 overexpression also causes an increase in leukocytes, which is consistent with its role in other systems (7,21). Importantly, we have shown that khvIL-10 could also increase leukocyte numbers in this heterologous setting, acting via the IL-10 receptor subunit, IL-10R1.…”
Section: Resultssupporting
confidence: 89%
“…When administered to pregnant rhesus monkeys, this cytokine gains access to the amniotic cavity where it harbors with a half-life of 13.2 hours [65], which is higher than the half-life of 2-4 hours in the circulation of volunteers following subcutaneous administration [210]. The longer half-life of IL-10 within the amniotic cavity indicates that the amniotic cavity may provide a depot-like effect prolonging the effectiveness of the treatment [65].…”
Section: Il-10 Administration: Possible Implications In the Preventiomentioning
confidence: 99%
“…Clinical trials in which IL-10 was administrated systemically to healthy volunteers have demonstrated that, at doses associated with biological activities, this cytokine has minimal side effects [209][210][211][212][213], including a mild flu-like syndrome [210], transient mild to moderate neutrophilia, monocytosis, lymphopenia (dramatic reductions of 40-70% in circulating lymphocytes expressing the T cell markers CD2, CD3, and CD7), and a delayed decrease of platelet count [209,210]. Thus, IL-10 has been proposed as a candidate for treatment of bacterial sepsis, and more generally as an effective anti-inflammatory agent [72] and clinical trials have shown that its systemic administration is followed by modest but significant improvement of psoriasis [214,215], Crohn's disease [216], rheumatoid arthritis [217], and chronic hepatitis C infection [218].…”
Section: Il-10 Administration: Possible Implications In the Preventiomentioning
confidence: 99%
“…Disease-associated proinflammatory cytokines such as TNF-a, IL-1b, IL-12, and IL-17 were reduced by half in some studies, indicating a pharmacodynamic activity (43). However, the suppression of IL-1 and TNF-a lasted only as long as the serum concentration of IL-10 was sufficiently elevated, returning to high values 24 hours after the IL-10 injection (44). Nevertheless, in early clinical studies encouraging efficacy of IL-10 was observed in psoriasis, hepatitis, and Crohn disease.…”
Section: Recombinant Human Il-10 Induces Ifn-g and Granzymes In Clinimentioning
confidence: 99%